Extraction and Characterization of Pectin from Kepok Banana Peel and Its Application as a Base Material for Edible Coating on Strawberries - Elinda Fithriana; Refilda; Yefrida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Strawberries are fruits rich in nutrients and bioactive compounds, but have a short shelf life due to their high respiration rate. The use of edible coatings from natural ingredients such as pectin can help extend the shelf life and maintain the quality of strawberries. This study aims to extract pectin from banana peels, characterize the pectin obtained, and apply it as a base material for edible coating for strawberries. The edible coating solution was made from kepok banana peel pectin (1%), carboxymethyl cellulose (1%), and glycerol (1%). The results of the extraction of banana peel pectin obtained an equivalent weight value of 695.76 mg, degree of esterification 71.71%, methoxyl content 7.98%, pH 2.99, antioxidant capacity 19.845 mgAA/gFW, FTIR results identify the main functional groups of pectin (C-H, O-H, and C-O-C), XRD Shows the amorphous structure of pectin. Edible coating of kepok banana peel pectin exhibits a bright colour with a tendency towards green and blue. Strawberries coated with an edible film derived from kepok banana peel pectin were monitored over a 6-day period (days 0 to 6) at room temperature (25°C). The coating effectively delayed visible decay until day 4, with cumulative weight loss reaching 33.33% by day 6. Contribution to Sustainable Development Goals (SDGs):SDG 6: Good Health and Well-beingSDG 11: Industry, Innovation, and InfrastructureSDG 13: Responsible Consumption and ProductionSDG 15: Climate Action